When sex is more than just sex: evaluating police perspectives regarding the challenges in interviewing victims of sexual offences in Jamaica - Elntib, Stamatis (Policing and society, 2020)
Rates of sexual assault remain high in Jamaica, although victims are often reluctant to report incidences to the police. Those cases which are reported by victims are investigated by the Jamaica Constabulary Force's Centre for Sexual Offences and Child Abuse (CISOCA). Whilst improvements have been noted in recent years, human rights organisations have highlighted on-going limitations of such investigations and the effective interviewing of victims. Despite this, a paucity of relevant research has prevented the development of empirically driven training aimed at supporting practitioners to deal with everyday challenges while interviewing vulnerable victims in Jamaica. Consequently, the present study sought to assess the challenges involved in interviewing victims of sexual offences in Jamaica and the cultural factors that may underline them. In-depth, semi-structured interviews were conducted with 41 police interviewers using thematic analysis to interpret the data. Analysis showed that organisational challenges such as training, expertise and capacity deficiencies, and early mishandlings with victims were detrimental to the quality of the interviews conducted. Psychological challenges included the need to be adaptive during interviews, spotting and dealing with deception, and separating work and personal life. Two key cultural factors were also revealed: the misconception that sex is just sex which reduced victim cooperation and a trend for attitude-shifting through policies which hinted that the Jamaican police culture towards victims changes gradually as new policies are introduced while victims are reportedly more willing to report the crimes against them.